Strategi Komunikasi Dinas Perpustakaan Kabupaten Polewali Mandar dalam meningkatkan Minat Baca Pemustaka - Muhammad Syaeba; Masyhadiah Masyhadiah (Al-MUNZIR, 2022)
The purpose of this study was to determine the communication strategy used by the Polewali Mandar Regional Library and Archives Service in increasing reading interest, especially in the Polewali Mandar area. The method in this study is a qualitative research method, the researchers conducted in-depth interviews with informants, namely the librarian of the Polewali Mandar Regency Library and Archives Service. The results showed that the communication strategy carried out was aimed at the community and school students. The message conveyed is the activities held in order to increase interest in reading the program targets. The impact is very good because the enthusiasm of the community and school students is very high in welcoming activities in the form of storytelling competitions and speaking competitions at the central level, in collaboration with literacy groups in Balanipa and mobile library activities. the implications of this communication strategy are very clear changes in the increase in reading interest, in 2018 elementary school students, namely 41% boys, 45% female elementary school students then in 2019 there was an increase in reading interest in elementary school students, namely male students increased 44% and female students to 46%, there is real progress from the communication strategy that has been implemented to increase interest in reading.Keywords: Communication Strategy, Interest in Reading, Library. Regional Library and Archives Service